WORKFORCE BIG DATA ANALYTICS AND PRODUCTION EFFICIENCY: A Manager’s Guide - BAGSHAW, KARIBO BENAIAH (Archives of Business Research, 2017)
Abstract The study investigates the use of workforce big data analytics as a tool to guide production managers to boost production efficiency while also ascertaining the level of awareness in the use workforce analytics amongst production managers. The study adopted survey research design and questionnaire were distributed to 20 respondents comprising of all Production Managers of the 20 Manufacturing Companies understudied. Data generated was analyzed using averages and scores. The outcome of the analyses showed that only 30% of the manufacturing companies had established and understood workforce plan while 70% did not have. Again the study showed that only 25% production managers agreed that the use of workforce big data analytics is necessary to boost production efficiency. Further findings showed that 75% of the managers admitted that their production was below average of which 40% of the managers ascribed their dismal performance to excessive manpower downtime which is a by-product of workforce scheduling. Based on the findings, it can be concluded that the use of workforce big data analytics is a more significant and important factor in boosting production efficiency.